A historical commentary on St Paul's epistle to the Galatians - Ramsay, William Mitchell, Sir, 1851-1939 (London, UK Hodder and Stoughton, 1900)
Includes bibliographical references.
Donated by the late Thomas Denton.
Keywords: Bible. N.T. Galatians -- commentaries